Peculiarities of blood rheology in patients with chronic generalized periodontitis combined with gastrointestinal tract disturbances - V. F. Kiritchuk; V. Yu. Shirokov (Бюллетень сибирской медицины, 2003)
The aim of investigation is to study blood rheological properties in patients with chronic generalised periodontitis combined with gastrointestinal tract disturbances. 205 patients have been examined including those with erosive ulcerous involvement of gastroduodenal area — 51, with stomach ulcer and duodenal ulcer — 62, with chronic colitis — 39, with nonspecific ulcer colitis — 53. Blood viscosity properties, indices of erythrocyte aggregation and deformability, rate of oxygen delivery to tissues have been evaluated by rotary viscometer АBR-2 (Russia). It has been revealed that blood rheological properties in patients with chronic generalised periodontitis combined with gastrointestinal tract disturbances had been disturbed, that was accompanied with the blood viscosity rise, erythrocyte aggregation increase and with the decrease of deformability and rate of oxygen delivery to tissues. The degree of violations in blood rheology indices was mostly expressed under chronic and plural erosions of gastroduodenal area, duodenal ulcer and severe course of chronic nonspecific ulcer colitis.